One-sided Arbitration Agreements in Government Contracts under the Law of Public Procurement - Alejos, Oscar (2019)
The arbitration agreement has its origin, by nature, in the free will of the parties who want to summit their controversies to arbitration, instead of the ordinary jurisdiction. However, in the case of the public contracts, the arbitration agreement does not have the same characteristics of free will, as they have in civil contracts, precisely because of the public nature of the authority, which means that they are subject to the legality principle instead of having free will. In this paper I will try to prove that, as a consequence of it, our legal framework produces one-sided arbitration agreements which benefit the public authorities who draft those agreements. In fact, the lack of possibilities for the contracting party to negotiate the content of the agreement allows the public authority to draft such content in a way that only benefit them and negatively affects the contractor, creating a situation of inefficiency. The legislator, aware of the problem, has enacted rules that seek to recognize rights to the bidder and restrict the discretionary powers of the authority; however, those measures are not good enough. In this scenario, I propose a solution which requires legal regulation in the content of the aforementioned agreements, in a way that can be granted, from an ex-ante regulation, that the arbitration agreement will be balanced.